La inclusión del Islam en España vista desde el Magisterio Social Católico - Villagrán, Gonzalo 1975- (2017)
If we consider Catholic social teaching as a tradition of social thought based on Christian revelation, this teaching’s reflection on Islam is already the beginning of interreligious dialogue. Catholic social teaching’s position on the inclusion of Islam is based on a main assertion, human dignity, developed then in the principles of religious freedom and the common good, as well as in dialogue as a main characteristic of its way of proceeding. These traits design a view of society similar to a moderate communitarianism. From this point of view we can evaluate the Spanish inclusion model, strongly inspired by Catholic social thought. In fact, the Spanish model follows closely these main principles. However, we can also notice how this model drifts apart from Catholic social teaching as it does not demand the State to protect an objective common good or to promote interreligious dialogue. These can be the lines of the development of the model in the future.
Partimos de la comprensión del magisterio social católico como tradición basada en la revelación cristiana, lo que nos permite pensar la reflexión desde este magisterio sobre el Islam como un principio de diálogo interreligioso. A partir de aquí vemos que la posición del magisterio social se basa en el reconocimiento de la dignidad humana y se declina en dos grandes principios y una característica: los principios de la libertad religiosa y el bien común, y el diálogo como modo de proceder del magisterio social. Estas características nos dibujan el perfil de un comunitarismo moderado. Desde aquí podemos ver que el modelo de integración español, fuertemente inspirado por el pensamiento social cristiano, sigue bastante estos puntos aunque se aleja en cuanto que no pide al Estado una defensa del contenido del bien común ni invita al diálogo interreligioso. Estos pueden ser caminos de desarrollo de dicho modelo.
Keywords: Tradición; Diálogo Interreligioso; Bien Común; Libertad religiosa; dignidad humana; magisterio social